Influencia del ecosistema en las estrategias del mejoramiento genético de la yuca - Lozano, J.C.; Byrne, D.; Bellotti, Anthony C. (International Center for Tropical Agriculture, 1979)
Aspects related to breeding programs in cassava, the impact of past strategies and exptl results related to them are discussed. Even though sources of resistance have been identified for the majority of the diseases and pests, in addition to tolerance to adverse edaphic and climatic factors, it is difficult to combine these characters in one var. Therefore, emphasis has been placed on the identification of lines tolerant to various negative production factors (NPF). In Popayán and Carimagua ecosystems, clones resistant to some NPFs (edaphic, climatic and phytopathological) have been obtained. Breeding programs should be decentralized in order to produce var. with a wide range of resistatice to the majority of NPFs. (CIAT)